2001
DOI: 10.1086/321627
|View full text |Cite
|
Sign up to set email alerts
|

High‐Resolution Near‐Infrared Images and Models of the Circumstellar Disk in HH 30

Abstract: We present Hubble Space T elescope near-infrared camera and multiobject spectrometer observations of the reÑection nebulosity associated with the T Tauri star HH 30. The images show the scattered-light pattern characteristic of a highly inclined, optically thick disk with a prominent dust lane whose width decreases with increasing wavelength. The reÑected nebulosity exhibits a lateral asymmetry in the upper lobe on the opposite side to that reported in previously published Wide Field Planetary Camera 2 images.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
153
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(166 citation statements)
references
References 51 publications
13
153
0
Order By: Relevance
“…(23) it is also clear that the opening angle α of the disk around IRS1b has to be large enough (α ≈ 45 • ) to ensure that the gas density does not exceed the threshold for the thermal quenching even at R ≥ R 0 . Such a geometry reminds the profiles of the rotationally flattened, circumstellar envelopes observed towards low-mass YSOs at millimeter wavelengths (Koerner & Sargent 1995) and in the near-IR (Cotera et al 2001). If high-mass star formation proceeds as a scaled-up version of the low-mass case, rotationally flattened, thick disks/envelopes could characterize the earliest protostellar phase, when only a minor fraction of the available circumstellar material has been accreted onto the protostar.…”
Section: General Implications Of the Model For Ngc 7538 Irs1mentioning
confidence: 63%
“…(23) it is also clear that the opening angle α of the disk around IRS1b has to be large enough (α ≈ 45 • ) to ensure that the gas density does not exceed the threshold for the thermal quenching even at R ≥ R 0 . Such a geometry reminds the profiles of the rotationally flattened, circumstellar envelopes observed towards low-mass YSOs at millimeter wavelengths (Koerner & Sargent 1995) and in the near-IR (Cotera et al 2001). If high-mass star formation proceeds as a scaled-up version of the low-mass case, rotationally flattened, thick disks/envelopes could characterize the earliest protostellar phase, when only a minor fraction of the available circumstellar material has been accreted onto the protostar.…”
Section: General Implications Of the Model For Ngc 7538 Irs1mentioning
confidence: 63%
“…Furthermore, grain growth is probably the first step in the process of planet formation. For this reason, there has been intense interest in finding evidence for grain growth in circumstellar disks, with many observational claims for its discovery (Beckwith et al 1990;Beckwith & Sargent 1991;Mannings & Emerson 1994;Throop et al 2001;Cotera et al 2001;D'Alessio, Calvet, & Hartmann 2001;Calvet et al 2002;Wood et al 2002;Wolf, Padgett, & Stapelfeldt 2003) but also indications that in some disks the dust is not too different from ISM dust (Silber et al 2000;Stapelfeldt et al 2003;Wolf et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…If the dust is completely gray in the visible and near-infrared (i.e., the opacity is independent of wavelength), the dark lane thickness should be constant with wavelength; if the dust is chromatic (i.e., the opacity changes with wavelength), the dark lane should appear narrower at wavelengths at which the opacity is lower. Edge-on disks whose dark lanes are known to narrow toward longer wavelengths include Orion 114-426 (McCaughrean et al 1998), IRAS 04302+2247 (Padgett et al 1999), HH 30 (Cotera et al 2001), and HV Tauri C . Similarly, Shuping et al (2003) recently found that the outer radius of the Orion 114-426 silhouette disk decreases toward longer wavelengths.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations